THE FACTORS EFFECTIVE IN THE SALE OF TRADITIONAL FOOD IN RESTAURANTS - Emel MEMİŞ KOCAMAN (International Journal of Eurasia Social Sciences, 2018)
With the increasing consumer demand and interest, traditional food has become an important sales, marketing and promotion tool for the food and beverage business. This study was conducted to evaluate the availability and the objective of having traditional food in restaurant menus, and customer group that prefers traditional food the most according to the country, years of operation and seating capacity of the business. The study used a questionnaire and was conducted in 576 restaurant employees in Italy, Czech Republic and Turkey. The study found that most businesses have traditional food in their menus and that there is a significant difference between restaurants when compared according to the years of operation and seating capacity (p<0.05). There is also a significant difference between countries in terms of their customer group that prefer traditional food in restaurants (p<0.001). This study provides information for restaurant managers about traditional food.